2006
DOI: 10.1016/j.jmb.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Half of the Peroxisomal Cycling Receptor Pex5p is a Natively Unfolded Domain

Abstract: Targeting of most newly synthesised peroxisomal matrix proteins to the organelle requires Pex5p, the so-called PTS1 receptor. According to current models of peroxisomal biogenesis, Pex5p interacts with these proteins in the cytosol, transports them to the peroxisomal membrane and catalyses their translocation across the membrane. Presently, our knowledge on the structural details behind the interaction of Pex5p with the cargo proteins is reasonably complete. In contrast, information regarding the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 68 publications
1
68
0
Order By: Relevance
“…Binding of PTS1-containing cargo to the receptor is essential for import of the receptor-cargo complex, which can be rationalized in terms of the conformational change required to expose the N-terminal docking module which appears to be a natively unfolded domain (Carvalho et al, 2006). The N-and C-terminal regions of mammalian PEX5S without a bound ligand have been shown to interact with each other by a pull-down assay.…”
Section: Pex5p Receptormentioning
confidence: 99%
“…Binding of PTS1-containing cargo to the receptor is essential for import of the receptor-cargo complex, which can be rationalized in terms of the conformational change required to expose the N-terminal docking module which appears to be a natively unfolded domain (Carvalho et al, 2006). The N-and C-terminal regions of mammalian PEX5S without a bound ligand have been shown to interact with each other by a pull-down assay.…”
Section: Pex5p Receptormentioning
confidence: 99%
“…these proteins are sequestered by adding to the import reactions a vast excess of a recombinant protein comprising only the cargo protein-binding domain of Pex5p (TPRs-Pex5p), then insertion of Pex5p is no longer possible (46). As shown in Fig.…”
Section: E2d-mediated Ubiquitination Of Mammalian Pex5pmentioning
confidence: 99%
“…Functional and structural data revealed that Pex5p includes two separated, functionally distinct domains. The N-terminal domain is intrinsically disordered and capable to mediate all transport steps of the receptor cycle, including docking and pore formation as well as dislocation from the peroxisomal membrane (13)(14)(15). The C-terminal domain of the receptor consists of an array of tetratricopeptide repeat (TPR) domains and directly binds the PTS1 motif (16).…”
mentioning
confidence: 99%